2022
DOI: 10.1155/2022/4257359
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Strategies for Aberrant Lipid Metabolism Reprogramming and the Immune Microenvironment in Esophageal Cancer: A Review

Abstract: Esophageal cancer is of high importance to occurrence, development, and treatment resistance. As evidenced by recent studies, pathways (e.g., Wnt/β-catenin, AMPK, and Hippo) are critical to the proliferation, differentiation, and self-renewal of esophageal cancer. In addition, the above pathways play a certain role in regulating esophageal cancer and act as potential therapeutic targets. Over the past few years, the function of lipid metabolism in controlling tumor cells and immune cells has aroused extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 204 publications
0
2
0
Order By: Relevance
“…Our enrichment results also showed the fatty acid degradation and biosynthesis was regulated by methionine/cystine intake. It has been demonstrated that by regulating the level of fatty acid metabolism in esophageal cancer cells, it could lead to changes in inflammatory cell function in the tumor immune microenvironment and further affect the development and progression of esophageal cancer [ 68 ]. ACSL5 and ALAS2 were downregulated in MCR group, they were all involved in fatty acid metabolism and played different roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our enrichment results also showed the fatty acid degradation and biosynthesis was regulated by methionine/cystine intake. It has been demonstrated that by regulating the level of fatty acid metabolism in esophageal cancer cells, it could lead to changes in inflammatory cell function in the tumor immune microenvironment and further affect the development and progression of esophageal cancer [ 68 ]. ACSL5 and ALAS2 were downregulated in MCR group, they were all involved in fatty acid metabolism and played different roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed profiles of immune cell infiltration and differentially expressed genes (metabolic, immune-related, or others) in many cancers continue to be elucidated ( 7 , 16 , 17 ). Several metabolic factors have shown an association with pathogenesis and progression of various cancers ( 18 , 19 ) such as de novo lipid biosynthesis is a crucial regulator in the prostate cancer ( 20 22 ). An anecdotal observation metabolic health of the individuals may influence the prognosis and treatment of the cancers.…”
mentioning
confidence: 99%